1991
DOI: 10.1007/bf01993129
|View full text |Cite
|
Sign up to set email alerts
|

The influence of H1-, H2- and H3-receptors on the spontaneous and ConA induced histamine release from human adenoidal mast cells

Abstract: The effects of the H3-agonist R-alpha-methylhistamine (R-alpha-MeHA) and the H3-antagonist thioperamide on the spontaneous and concanavalin A (ConA) induced histamine release from human mast cells were tested and compared with the effect of some H1- and H2-receptor active substances. R-alpha-MeHA (10(-9)-10(-7) M) exerted no effect on histamine release whereas thioperamide increased the spontaneous release at 10(-6)-10(-4) M but inhibited the ConA induced release in a narrow concentration range (10(-6)-10(-5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Its spontaneous histaminereleasing effect was thought to indicate the presence of the H 3 receptor, but the differing effects on stimulated and unstimulated cells suggested that H 3 -independent mechanisms may be involved. The existence of the H 3 receptor on the human basophil has also been investigated, 18 but no modulation of IgE-mediated histamine release was observed after incubation with RAMHA and thioperamide. In addition, IgE-independent basophil mediator release was studied in atopic dermatitis patients by Bull et al and neither RAMHA nor thioperamide modulated histamine release.…”
Section: Discussionmentioning
confidence: 99%
“…Its spontaneous histaminereleasing effect was thought to indicate the presence of the H 3 receptor, but the differing effects on stimulated and unstimulated cells suggested that H 3 -independent mechanisms may be involved. The existence of the H 3 receptor on the human basophil has also been investigated, 18 but no modulation of IgE-mediated histamine release was observed after incubation with RAMHA and thioperamide. In addition, IgE-independent basophil mediator release was studied in atopic dermatitis patients by Bull et al and neither RAMHA nor thioperamide modulated histamine release.…”
Section: Discussionmentioning
confidence: 99%
“…H3 receptors were initially found on rat peritoneal and cutaneous (Ohkubo et al, 1994;Bissonnette, 1996) as well as on human adenoidal mast cells. (Bent et al, 1991) However, according to more recent data, they seem to be restricted to the central nervous system (Rozniecki et al, 1999). Expression of the H4 receptor has so far been described at the mRNA level with commercially available probes from cultured bone marrow-derived mast cells (Morse et al, 2001), and very recently also indirectly in receptor-deficient mice (Hofstra et al, 2003).…”
mentioning
confidence: 92%
“…The novel histamine H receptors were identified as inhibitory presynaptic autoreceptors on histamine-containing nerve terminals in the rat brain cortex but have since been shown to inhibit the release of various neurotransmitters both in the central and peripheral nervous systems. 2 Recent articles provide strong evidence for the presence of histamine H receptors at the different sites, including the rabbit middle cerebral artery endo-3,4 5 6 thelium,' guinea-pig aorta, mesenteric artery, rabbit saphenous artery, 7 guinea-pig myo- 8 9 cardium, guinea-pig ileum, guinea-pig lung and 10 11 I2 bronchiole, guinea-pig intestine, porcine small intestine, rabbit gastric glands, 14 human 15 adenoidal mast cells, human and rhesus monkey brain. 6 .The purpose of the present study was to determine whether histamine H receptors are localized on rat aorta endothelium and to assess their possible role in endothelium-dependent responses.…”
Section: Introductionmentioning
confidence: 99%